2015
DOI: 10.1007/978-3-319-22729-0_29
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Multidimensional Databases with Document-Oriented NoSQL

Abstract: Abstract. NoSQL (Not Only SQL) systems are becoming popular due to known advantages such as horizontal scalability and elasticity. In this paper, we study the implementation of data warehouses with document-oriented NoSQL systems. We propose mapping rules that transform the multidimensional data model to logical document-oriented models. We consider three different logical models and we use them to instantiate data warehouses. We focus on data loading, model-to-model conversion and OLAP cuboid computation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…MongoDB utilizes the document-oriented data model to store data as collections in documents [38]. Different from RDBMS, there is no fixed schema in MongoDB.…”
Section: Key-value Data Modelmentioning
confidence: 99%
“…MongoDB utilizes the document-oriented data model to store data as collections in documents [38]. Different from RDBMS, there is no fixed schema in MongoDB.…”
Section: Key-value Data Modelmentioning
confidence: 99%
“…We relate document-oriented databases to NoSQL databases, which are schema-less. Collections in this database comprising unique documents which are being used to store heterogeneous, unstructured and complex structures documents [21]. The document-oriented data model for the database is as shown in the Fig.…”
Section: Document Oriented Modelmentioning
confidence: 99%
“…Although several authors have observed that there is a need for data-model approaches to the design and management of NoSQL databases [9,10,11] [33] and in a column-oriented NoSQL database [34].…”
Section: Related Workmentioning
confidence: 99%